Cross-Border Collaboration as An HR System: Joint Training, Interoperability, and Trust - Yohannes Andriyus Wijaya; M. Irfani Hendri; Maria Christiana Iman Kalis (JURNAL MANAJEMEN MOTIVASI, 2026)
This study reviews 64 Scopus-indexed publications (2004–2026) to examine cross-border collaboration as a human resource (HR) management system in border regions. Using the PRISMA protocol and thematic analysis, it addresses HR retention and competency challenges, the effectiveness of joint training and cross-institutional standard operating procedures, and evidence-based policy strategies. Four themes emerged: inter-agency trust, system and data interoperability, adaptive joint training design, and multi-actor governance. Collaboration effectiveness depends on combining structural factors (regulatory harmonization, shared legal frameworks) with relational factors (interpersonal trust, cultural sensitivity, informal communication). The study proposes an integrated cross-border HR framework relevant to border governance in Indonesia. Keywords: Cross-Border Collaboration; Joint Training; Interoperability; Trust; Border HR; Public Service; Cross-Institutional Governance